PERAN BIMBINGAN KELOMPOK DALAM MENINGKATKAN KEPERCAYAAN DIRI (SELF DISCLOURE) SISWA DI SMPN 2 BAHOROK DESA TIMBANG LAWAN - Irna Delima Nasution; Sri Rahayu; Sholihah Puspita; Vida Amara; Abdul Aziz Rusman (STKIP Subang, 2023)
This research aims to investigate the role of group guidance in increasing students' self-confidence. The research subjects consisted of Guidance and Counseling (BK) teachers and students of SMP N 2 Bahorok, Timbang Lawan Village. This research uses a qualitative approach with data collection techniques in the form of observation and interviews. The research results show that group guidance is carried out through organizing competitions, such as fashion shows, short surahs, and the call to prayer. The impact of this group guidance is increasing students' self-confidence, improving relationships between guidance and counseling teachers and students, as well as validating the effectiveness of the group guidance method. The conclusion of this research is that group guidance carried out by guidance and counseling teachers, especially through holding competitions, is able to increase students' self-confidence. This competition encourages students to feel more confident in themselves, while strengthening the relationship between teachers and students in the learning process.